Formation of Spaced Cleavage and Concurrent Mass Removal of Si02, Meguma Goup Metagreywackes, Goldenville, Nova Scotia - Fueten, F.; Clifford, P.; Pryer, L.; Crocket, J.; Thompson, M. (Atlantic Geology, 1986)
Increasing inequancy and decreasing fluctuation of long axes of quartz grains fro* lithons to cleavage zones in Heguna Group metagreywackes indicate an increase in strain. This strain increase is best ascribed to pervasive pressure solution in which quartz grains are trimmed to yield nearly rectangular sections in cleavage zones, as compared to their irregular outlines in lithons. Shortening calculated from a one-dimensional strain model reaches 60-7OZ in cleavage zones. Comparable values of shortening are calculated from modal analyses, and from chemical analyses of cleavages and lithons. The Implication of such shortening is that about ten percent of all the quartz in the original rock has been removed from the immediate system. This demands volumes of water about one order of magnitude greater than any likely content of connate water. The transport system was a dynamic one, involving most of the rock volume.